RECOBRIMENTO DE APATITAS “IN VITRO” SOBRE TITÂNIO – INFLUÊNCIA DO TRATAMENTO TÉRMICO - de, L. C. [UNESP]; de Assis, C. M. [UNESP]; Lia Fook, M. V. [UNESP]; Dos Santos, M. L. [UNESP]; Guastaldi, A. C. [UNESP] (Ecletica Quimica, 2003)
Commercially pure titanium (cp-Ti), and some of its alloys are considered very important in the medical field because of its excellent biocompatibility and mechanical properties. Recently a simple chemical method was introduced to induce the bioactivity of these inert metallic materials. In this work, the biomimetic chemical process has been used to modify the cp-Ti surface with the deposit of a layer of apatite. The main objective consisted in studying the influence of the thermal treatment on the evolution of the crystallinity of the deposited phases. X-ray diffraction and scanning electron microscopy techniques showed that the apatite coatings with thermal treatments between 400 and 600 °C presented low crystallinity similar to the biological apatites. Above 700 °C, the apatite coatings appeared more crystalline, exhibiting a mixture of hydroxyapatite, octacalcium phosphate and magnesium phosphate.
Keywords: Biomaterials; Biomimetic process; Coatings; Hydroxyapatite; Titanium